2019
DOI: 10.1111/jgh.14934
|View full text |Cite
|
Sign up to set email alerts
|

Fundic gland polyp prevalence according toHelicobacter pyloriinfection status

Abstract: Background and AimThe prevalence of fundic gland polyp (FGP) occurrence has not been clarified in individuals with Helicobacter pylori infection post‐eradicated status. This study was performed to examine the relationship between FGP prevalence and H. pylori infection status.MethodsWe enrolled 3400 subjects (2185 male subjects and 1215 female subjects; mean age 54.7 ± 9.5 years) with known H. pylori infection status and who underwent an upper gastrointestinal endoscopy examination as part of an annual check‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…In contrast, the relationship between HP infection and the occurrence of fundic gland polyps has not yet been elucidated. Studies have shown that HP infection is negatively correlated with the incidence of fundic gland polyps (9), and the HP infection rate in patients with fundic gland polyps is significantly lower than that in patients with hyperplastic polyps (10). However, some studies have mentioned that although HP infection has been confirmed to be related to the occurrence of hyperplastic polyps and inflammatory fibrous polyps, there is no clear relationship between fundic gland polyps and HP infection (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the relationship between HP infection and the occurrence of fundic gland polyps has not yet been elucidated. Studies have shown that HP infection is negatively correlated with the incidence of fundic gland polyps (9), and the HP infection rate in patients with fundic gland polyps is significantly lower than that in patients with hyperplastic polyps (10). However, some studies have mentioned that although HP infection has been confirmed to be related to the occurrence of hyperplastic polyps and inflammatory fibrous polyps, there is no clear relationship between fundic gland polyps and HP infection (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1990s, FGPs were reported to be prevalent in 0.21%-2.0% of patients undergoing esophagogastroduodenoscopy[ 9 - 11 ]. However, since the launch of PPIs around 1990, an increase in the number and size of FGPs associated with PPI use has been reported, and reports since 2000 have shown an obvious increase in the prevalence of FGPs at 5.9%-30.3%[ 12 , 13 ]. FGPs have been reported to occur in 13.6%-36% of patients receiving PPI therapy[ 5 , 14 ].…”
Section: Prevalence Of Fgp With or Without Dysplasiamentioning
confidence: 99%
“…Carmack et al [ 1 ] compared the prevalence of various polyps in the United States population over a one-year period from April 2007 to March 2008 with that in previous reports and noted an increase in FGP prevalence with PPI use. In addition, FGPs can occur in Helicobacter pylori ( H. pylori )-negative stomachs[ 1 , 12 , 13 ]. In the future, considering that the H. pylori infection rate has been decreasing in recent years[ 15 , 16 ], the prevalence of FGPs is expected to further increase along with the widespread and frequent use of PPIs.…”
Section: Prevalence Of Fgp With or Without Dysplasiamentioning
confidence: 99%
See 2 more Smart Citations